Outcome analysis of 215 patients with parotid gland tumors: a retrospective cohort analysis. Issue 1 (December 2015) - Erovic, Boban; Shah, Manish; Bruch, Guillem; Johnston, Meredith; Kim, John; O'Sullivan, Brian; Perez-Ordonez, Bayardo; Weinreb, Ilan; Atenafu, Eshetu; de Almeida, John; Gullane, Patrick; Brown, Dale; et al.
Abstract Background To identify prognostic factors in patients with parotid gland carcinomas who were treated at the Princess Margaret Hospital. Methods Clinical outcome of two hundred fifteen patients with malignancies of the parotid gland was evaluated over a 16-year period. Results Two-hundred-fifteen patients with adenoid cystic carcinoma (n  = 20), adenocarcinoma (n  = 19), acinic cell carcinoma (n  = 62), basal cell adenocarcinoma (n  = 7), carcinoma-ex-pleomorphic adenoma (n  = 18), mucoepidermoid carcinoma (n  = 70) and salivary duct carcinoma (n  = 19) have been included. The 5- and 10-year overall and disease-free survivals were 80.62 %/69.48 % and 74.37 %/62.42 %, respectively. Multivariable analysis showed that age greater than 60 years, advanced pN classification, histopathological grade and the presence of lymphovascular invasion significantly worsened overall and disease-free survival. Univariable analysis revealed periparotid lymph node involvement was associated with decreased overall (p  < 0.0001) and disease-free survival (p  < 0.0001). Conclusions In addition to age, pN classification, histopathological grade, perineural invasion, and lymphovascular involvement, periparotid lymph node metastasis appears to be an important prognosticator in parotid gland malignancy.